Kampung IT - Menuju Pembangunan Berkelanjutan - Rudolf Wirawan (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2018)
Traditional agricultural activities in Indonesia can play a significant part in sustainable development. A key challenge faced is the trend towards urban concentration, which reduces this potential due to the reduction in agricultural support as individuals relocate to the main cities. This paper explores the concept of ‘Smartvillages’, which involves bringing farming development and IT development activities together to enable outcomes that achieve economic growth through sustainable practices whilst helping to address climate change.  Kegiatan pertanian tradisional di Indonesia dapat memainkan peran penting dalam pembangunan berkelanjutan. Tantangan utama yang dihadapi adalah kecenderungan konsentrasi perkotaan, yang mengurangi potensi ini karena pengurangan dukungan pertanian sebagai individu pindah ke kota-kota Besar. Makalah ini mengeksplorasi konsep ‘Kampung IT, yang melibatkan pengembangan pertanian dan kegiatan pengembangan TI secara bersama-sama untuk memungkinkan hasil yang mencapai pertumbuhan ekonomi melalui praktik berkelanjutan sambil membantu mengatasi perubahan iklim.